Development of a complex solution for a human-robot interaction and operators training using VR-integrated DT framework - Palazhchenko, Yevhen; Shendryk, Vira; Meyer, Georg (Technology audit and production reserves, 2026)
The object of research is the process of managing human-robot interaction through the virtual reality-integrated digital twin system. The problem addressed in the research is that, despite active development of architectural solutions, there are barriers to fundamental research and operator training due to the prohibitive costs, technical complexity, and proprietary restrictions of industrial-grade robotic hardware. The obtained results are the creation of a comprehensive, scalable, and flexible digital twin architecture, implemented through a functional prototype. The prototype digital twin framework is an extensible tool for testing research strategies and can be adapted for specific tasks or equipment. The implementation synchronizes a low cost 6-degrees-of-freedom manipulator with its digital model using the Unreal Engine. Analysis of the application areas of the developed system highlights the potential of virtual reality to improve human-robot interaction. These results were made possible by a complex approach combining architectural design and experimental prototyping. Unlike industrial solutions, which focus on specific technologies, a general approach to system design was applied. A significant advantage of focusing on general principles is that they can be developed without recourse to using complex real systems, which are associated with safety, accessibility, and cost issues. The proposed solution is designed to enable systematic testing of a wide range of user interface designs, situational awareness tools, interaction, and collaboration strategies in a risk-free virtual environment. The underlying design and software will be publicly available, enabling researchers to use a standardized yet flexible approach to develop human-robot interaction systems based on the results presented in this research.